From Habermas’ Critical Theory to Discurse Theory of Law and Democracy: Overcoming the “system/lifeworld” dichotomy - Ortega-Esquembre, César (ENDOXA, 2021)
The aim of this paper is to analyse the consequences of Habermas´ discourse theory of law and democracy [1992] for his model of critical theory as a theory of communicative action [1981]. I defend that such a theory means Habermas´ attempt to correct the undue and previously maintained dichotomization between “system” and “lifeworld.” To support this interpretation, I first present the meaning of Habermas´ critical theory as a theory of communicative action by focusing on the “system/lifeworld” dichotomy, on the thesis of internal colonization and on some problems associated with this scheme. Second, I analyze the key elements of the discourse theory of law and democracy. Lastly, I show that this theory allows Habermas to correct some of the above-mentioned problems.